2015
DOI: 10.1097/md.0000000000000906
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationships of Coping Styles and Professional Burnout Among Physiotherapists

Abstract: Burnout is a pathological syndrome in which emotional exhaustion (EE), depersonalization (DEP), and a reduced sense of personal accomplishment (PA) develop in response to prolonged occupational stress. Those working in the physiotherapy profession appear to be at risk for professional burnout brought on by the specific character of the medical professions, involving continuous contact with patients and associated stress, as well as poor working conditions. However, literature data concerning the scale of profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
4
16
1
1
Order By: Relevance
“…However, our study results suggest any different interrelationships. The results of the analysis in our study confirm the predictions concerning the positive effects of problem-focused coping of the work-related burnout symptoms [28].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, our study results suggest any different interrelationships. The results of the analysis in our study confirm the predictions concerning the positive effects of problem-focused coping of the work-related burnout symptoms [28].…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, they found that this coping style was preferable under poor organizational conditions Task-oriented coping was associated with decreased risk of burnout, while emotion-oriented coping was associated with increased risk of burnout for healthcare professionals in a large Canadian study emergency department [27]. Problem-focused coping is a good indicator of compassion satisfaction but it is not correlated to compassion fatigue or burnout [28]. However, our study results suggest any different interrelationships.…”
Section: Discussioncontrasting
confidence: 54%
“…Alguns estudos foram realizados no ambiente hospitalar sem especificar se foram realizados com trabalhadores que atuam em ambulatório, em enfermaria ou em Unidade de Terapia Intensiva 4,9,19,20,22,23,24 .…”
Section: Discussionunclassified
“…Similarly, DI was linked to an emotion-oriented coping style (Oginska and Oginska-Bruchal 2014). Both neuroticism and the emotion-oriented stress coping style are recognized as risk factors of burnout symptoms (Nowakowska-Domagala et al 2015;van der Wal et al 2016). This dyad may be further supplemented by high amplitude of the rhythm; this combination may give rise to a specific pattern of circadian functioning marked by high emotional liability or negative emotionality, which predisposes the individual to psychophysical exhaustion and disillusionment.…”
Section: Hypothesismentioning
confidence: 99%